1990
DOI: 10.1139/f90-093
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Submergent Plant Bed Biovolume using Acoustic Range Information

Abstract: 1990. Estimation of submergent plant bed biovolume using acoustic range information. Can. J. Fish. Aquat. Sci. 47: 805-81 2.Acoustic nieasurements of the distance between the water surface, top of the aquatic plants, and bottom of the water column were made using chart recording echosounders. The vertical cross sectional area (m2), height (m), biovolume (rn3), of aquatic plant beds and variances were computed for three surveys of Devils Lake, Oregon, in May, July, and September, 1986 when coefficients of varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
0
17
0
Order By: Relevance
“…This greater expense was primarily attributed to the greater labour costs associated with harvesting. Thomas et al (1990) also found the acoustic technique had a higher precision than from quadrat harvests, providing a 5-to-18 fold greater capability to detect a change in the mean. However, the two techniques were comparing slightly different characteristics of the macrophyte community.…”
Section: Al Comparison Of Two Biomass Estimation Techniquesmentioning
confidence: 90%
See 4 more Smart Citations
“…This greater expense was primarily attributed to the greater labour costs associated with harvesting. Thomas et al (1990) also found the acoustic technique had a higher precision than from quadrat harvests, providing a 5-to-18 fold greater capability to detect a change in the mean. However, the two techniques were comparing slightly different characteristics of the macrophyte community.…”
Section: Al Comparison Of Two Biomass Estimation Techniquesmentioning
confidence: 90%
“…Sparse vegetation included a third variable which was the percent vertical cover of vegetation on the echosound tracings. Thomas et al (1990) compared SCUBA quadrat harvesting to the acoustic method proposed by Maceina and Shireman to determine the relative costs associated with each technique. Over three years of research, the quadrat harvesting method was shown to be 1.9 times more expensive than sampling with an echosounder.…”
Section: Al Comparison Of Two Biomass Estimation Techniquesmentioning
confidence: 99%
See 3 more Smart Citations